The genesis of the " teenager`s psychological potential" concept - Svatenkova, Tetyana (Psychological Prospects Journal, 2022)
Purpose of the article is to investigate the specifics of the scientific opinion’s regarding development of the teenager`s psychological potential. Methods. Theoretical: exploratory and analytical methods such as relevant literature analysis on the topic, comparison, analogy, systematization and juxtaposition. The results. The problem of the individual`s potential is a centuries-old practice material in scientific knowledge that has not yet been fully mastered by science, primarily in the part where the ideal of human development appears as something that has an independent ontological status and is potentially characteristic of a person. This problem`s formulation creates the need to understand the potential as different from the actual form of real existence. The potential self is even more real than the actual self of a person, since it is able to induce him to change his psychological and physical state in some sense. The concept of the individual`s psychological potential is the most valuable methodological achievement in the 20th century`s psychology developed and such that continues to be developed in the XXI century. The individual`s psychological potential in psychological science is usually perceived as (1) unused abilities and skills, (2) unexpressed activity, unexpressed initiative. The rapid science development and the active transformation of the education system demonstrate not the utopian nature, but the reality of the transhumanism provisions and the new concept of human evolution. The some children’і potential is rhetorically and philosophically combined with the potential of all humanity. Today, gifted children, the so-called "high-potential subjects", are still often depicted in academic and political discourse as hidden resources of humanity, ready to improve it given the right stimuli, and the education role in finding and using these stimuli is brought to the foreground. Conclusions. The article highlights the results of scientific and theoretical research on the views` development on the individual`s potential in adolescence. A short historical and psychological excursion highlights the main results of scientific and educational discussions around this concept and the evolution of the view from identifying, measuring and controlling its development to supporting and believing in the inexhaustibility of the each individual`s potential, obvious achievements` regardless.